Revolt on the right : explaining support for the radical right in Britain - Ford, Robert Anthony 1980- (Routledge studies in extremism and democracy, 2014)
"Since 2009, the UK Independence Party (UKIP) has become the most successful challenger to the main parties in postwar English politics. Yet with the radical right on the rise, important questions remain unanswered. What trends in modern Britain have made the rise of UKIP possible? How has the party modified its organization, strategy and ideology in the quest to forge ties with voters? Who is voting for the populist radical right in Britain, and why? To what extent, if at all, are UKIP supporters the mirror image of radical right voters in Europe, and where might the party go next? Based on an unprecedented amount of data, from surveys of UKIP voters to extensive interviews with UKIP insiders, Robert Ford and Matthew Goodwin explore the wider trends that gave birth to UKIP, how the party has evolved, and who is shifting behind UKIP at elections. The book provides unprecedented insight into public support for the radical right in Britain, and contains important insights for those who are tasked with responding to the radical right challenge"--